Does Women’s Empowerment Improve Yields and Income? Evidence from Rice Farmers in Rwanda - Ngango, Jules (Asian Journal of Agriculture and Rural Development, 2022)
This study aimed to assess the effects of women’s empowerment in agriculture on rice yield and income in rural Rwanda. A multi-stage stratified sampling procedure was used to collect data through structured questionnaires (including both open-ended and closed questions). A sample of 561 rice farmers drawn from the Eastern and Western provinces of Rwanda was used. The study used an instrumental variable to estimate the causal impacts of women’s empowerment, and controlled for the potential endogeneity of the same. The findings of the study showed that women’s empowerment has a positive impact on rice yield and income. Overall, the study results call for policy interventions promoting female participation in financial inclusion mechanisms, farmers’ cooperatives, and agricultural production decisions. In addition, the results highlighted the importance of building strategies and mechanisms for increasing women’s control and decisions over assets. The study makes contributions to the empirical literature on the United Nations Sustainable Development Goals, such as achieving gender equality, women’s empowerment, and food security in developing countries. Future research should attempt to use nationally representative panel data to fully understand the effects of women’s empowerment on rice productivity and other income outcomes.